Exploring the Role of Digital Transformation in Mitigating Accounting Fraud: A Cybersecurity Perspective - Abu-Dabaseh, Farah; Khtatbeh, Mohamed Mahmoud; Al’Ararah, Kayed; Alassuli, Abdalla (International Review of Management and Marketing, 2025)
Artificial intelligence, blockchain, and big data analytics have long disrupted business functions through digital transformation. While these innovations enhance the efficiency of operations and amplify the possibility of fraud detection, they also create avenues for fraud modulation that could conceivably heighten accounting fraud risk. This paper would go deep into how digital transformation influences accounting fraud risks, with a special focus on the role of cybersecurity maturity. Extensive research into the benefits of digitalization has not considered how cybersecurity maturity influences the effectiveness of such technologies in fraud risk mitigation. This study used a quantitative approach based on data collected from 204 employees of audit and accounting firms in Jordan. We assessed the relationship among the constructs using structural equation modeling with partial least squares. The results highlight the significant negative relationship that occurred between the accounting fraud risks and digital transformation, showing that digital technologies decrease fraud vulnerabilities when implemented effectively. Beyond the aforementioned, cybersecurity maturity proved to play a crucial role in moderating and strengthening the ability of digital transformation to mitigate fraudulent cases. These findings underline the need for organizations to go along with technological advancements by implementing appropriate cybersecurity frameworks in order to reap maximum benefits from digital transformation. In this light, the combination of technological innovation with integrated and mature security protocols can help an organization reduce fraudulent risks and work toward strengthening its financial integrity. Thus, this remains a valuable contribution to scholarship, assisting organizations and policymakers in navigating the complexities associated with the dual imperatives of digital transformation and fraud prevention in today’s digital era.